Development of the Mini Smart Cashier Application to Improve the Counting Ability of Students with Mild Intellectual Disabilities - Resvi Fitri; Pujaningsih; Muhamad Aflaha Rijal (Newinera Publisher, 2026)
This study aims to develop the Mikacer (Mini Smart Cashier) application as an Android-based counting aid to improve the ability to count money for students with mild intellectual disabilities phase D at SLB Negeri 2 Padang. Based on Piaget's cognitive development theory, Vygotsky's Scafolding, and the principles of Universal Design (UD) in learning media, Mikacer is an assistive technology designed as an adaptive and interactive money counting medium, and is easily accessible to all students who need it. The research method used the Design, Development, and Research (DDR) procedure from Richey and Klein, which produced the Mikacer (Mini Smart Cashier) mobile application with ten students with mild intellectual disabilities at a special needs school (SLB) as subjects. Data collection techniques used were observation, interviews, questionnaires, and performance observation. The results of this research are an Android-based application available on the Google Play Store for direct download. The application contains a step-by-step cashier simulation menu for calculating the amount of money, reducing money, calculating total purchases and calculating change in simple purchases. After being validated by six expert validator teams, the product results are in the very feasible category and the validation results can be used according to revisions and suggestions. Interventions to improve the ability to count money for students with mild intellectual disabilities use the Mikacer application that has been developed. Based on the results of performance observations from all subjects, they succeeded in improving their counting abilities from the initial baseline, intervention and final baseline.